Inequalities in English child protection practice under austerity: A universal challenge?. Issue 1 (7th July 2017) - Bywaters, Paul; Brady, Geraldine; Bunting, Lisa; Daniel, Brigid; Featherstone, Brid; Jones, Chantel; Morris, Kate; Scourfield, Jonathan; Sparks, Tim; Webb, Calum
Abstract: The role that area deprivation, family poverty, and austerity policies play in the demand for and supply of children's services has been a contested issue in England in recent years. These relationships have begun to be explored through the concept of inequalities in child welfare, in parallel to the established fields of inequalities in education and health. This article focuses on the relationship between economic inequality and out‐of‐home care and child protection interventions. The work scales up a pilot study in the West Midlands to an all‐England sample, representative of English regions and different levels of deprivation at a local authority (LA) level. The analysis evidences a strong relationship between deprivation and intervention rates and large inequalities between ethnic categories. There is further evidence of the inverse intervention law (Bywaters et al., 2015): For any given level of neighbourhood deprivation, higher rates of child welfare interventions are found in LAs that are less deprived overall. These patterns are taking place in the context of cuts in spending on English children's services between 2010–2011 and 2014–2015 that have been greatest in more deprived LAs. Implications for policy and practice to reduce such inequalities are suggested.